The construction of spatial iinvasion of carcinogen risk in scientific discourse : a corpus- based study - Khalil, Huda H.; Al-Zubaidi, Nassier A. G. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Scientific discourse is devoted, in many occasions, to transmitting knowledge about the risk of proximity to carcinogens; e.g. living near nuclear power station may cause cancer because of the emitted radiation which spreads around. No previous study has attempted to investigate the linguistic manifestation of the spatial perspective of carcinogen risk. The present paper aims at investigating the construction of the spatial invasion of carcinogen risk in scientific discourse to promote people to take preventive measures. To achieve this aim, Cap’s (2013) proximization theory of crisis and treat construction is employed. The theory provides three proximization strategies: spatial, temporal and axiological. The spatial proximization strategy, in particular, is adopted in the analysis. The analysis procedure is both qualitative and quantitative. Calculations are performed by corpus linguistics. AntConc software is used for this purpose. The corpus analysis tools used are word list, concordance, file view, cluster/ N- gram, wildcard * and the file view tool. The corpus consists of a set of scientific articles which are combined by the researchers to form the corpus. Results have revealed that scientific discourse employs various linguistic tools to construct the special proximization of carcinogen risk. However, the linguistic tools are employed with different rates to achieve certain cognitive pragmatic aims.